Psychological Capital Scale: A Study on the Psychometric Properties of Employees in Malaysia - Seow Ling Ooh; Chua Bee Seok; Ismail Maakip (Universitas Ahmad Dahlan, 2020)
Since its inception in 2007, psychological capital has been gaining more and more attention. Nonetheless, zero studies had been done on the psychometric properties of the 24-item Psychological Capital Questionnaire (PCQ) in Malaysia. Therefore, the present study examined the reliability and validity of the questionnaire. A total of 420 Malaysian government employees participated in this study. Findings revealed that the PCQ demonstrated a satisfactory level of psychometric properties in Malaysia after five items were excluded. Hence, the Psychological Capital Questionnaire (PCQ) could be used for Malaysian employees to discover positive contributions to psychological capital in the Malaysian workplace setting.Â